2017
DOI: 10.1002/mrc.4626
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic nuclear polarization studies of nitroxyl spin probes in agarose gel using Overhauser‐enhanced magnetic resonance imaging

Abstract: Agarose is a tissue-equivalent material and its imaging characteristics similar to those of real tissues. Hence, the dynamic nuclear polarization studies of 3-carboxy-2,2,5,5-tetramethyl-pyrrolidine-1-oxyl (carboxy-PROXYL) in agarose gel were carried out. The dynamic nuclear polarization parameters such as spin lattice relaxation time, longitudinal relaxivity, leakage factor, saturation parameter and coupling parameter were estimated for 2 mM carboxy-PROXYL in phosphate-buffered saline solution and water/agaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The ESR imaging, using nitroxyl probes, can able to provide such information, but OMRI has the advantage of providing coregistered images containing functional as well as anatomical information . Recently, the ESR and OMRI studies were reported that the optimized agent concentration was observed as 2 mM nitroxyl radicals . Many researchers reported the dynamic nuclear polarization studies at 2 mM agent concentration for ESR/OMR phantom imaging .…”
Section: Introductionmentioning
confidence: 99%
“…The ESR imaging, using nitroxyl probes, can able to provide such information, but OMRI has the advantage of providing coregistered images containing functional as well as anatomical information . Recently, the ESR and OMRI studies were reported that the optimized agent concentration was observed as 2 mM nitroxyl radicals . Many researchers reported the dynamic nuclear polarization studies at 2 mM agent concentration for ESR/OMR phantom imaging .…”
Section: Introductionmentioning
confidence: 99%